2021
DOI: 10.3390/seeds1010002
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Nitrate Treatment Is Associated with Modulation of Seed Water Uptake, Antioxidative Metabolism and Phytohormone Levels of Pea Seedlings

Abstract: (1) Background: Seed treatment with potassium nitrate (KNO3) has been associated with dormancy breaking, improved germination and enhanced seedling growth and uniformity in a variety of plant species. However, the KNO3 effect seems to be dependent on plant species and treatment conditions. (2) Methods: We describe the effect of incubation of dry pea seeds with different KNO3 concentration on water uptake kinetic, early seedling growth, antioxidant metabolism and hormone profile in pea seedlings. (3) Results: L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Salinity lowers the soil's water potential, which has been associated with a decline in the RWC of leaves and a drop in photosynthesis [43]. Numerous plant groups' hydration status has been shown to be improved by exogenous chemical supplementation [47][48][49]. The study's findings revealed that RWC decreased as a result of the salt stress (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Salinity lowers the soil's water potential, which has been associated with a decline in the RWC of leaves and a drop in photosynthesis [43]. Numerous plant groups' hydration status has been shown to be improved by exogenous chemical supplementation [47][48][49]. The study's findings revealed that RWC decreased as a result of the salt stress (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…KNO 3 was observed by Demir and Mavi to be effective in improving germination of the seeds of watermelon. In this regard, KNO 3 induced gibberellic acid levels which stimulated starch hydrolysis by increasing amylase activity and induced high germination and seedling growth . Some enzymes involved in cell division, nucleic acid metabolism, and protein synthesis use potassium as a cofactor.…”
Section: Discussionmentioning
confidence: 99%
“…10 Priming with low KNO 3 levels also improved the antioxidant activity in pea seedling. 9 Besides, the utilization of KNO 3 as a priming agent has been found to yield the highest percentage of seed vigor and germination ratio in linseed species, suggesting that this technique is a promising approach for enhancing the overall quality and yield potential of Linum usitatissimum seeds. 11 The utilization of plant growth regulators, such as phytohormones, enhances the productivity of different crops by employing priming mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Seed priming with KNO 3 is known to enhance germination, improve seedling growth, seedling vigor and drought tolerance through increased water imbibition, and activation of enzymes (amylases, xylanase, and dehydrogenases) and numerous ROS-scavenging antioxidants 32 . At the imbibition stage, seeds take up increased oxygen amount, resulting in accumulation of ROS shifting the redox state 49 . KNO 3 increases the activity of antioxidant enzymes such as SOD, CAT, ascorbate oxidase (AOX), and peroxidase (POX) in seedlings 49 .…”
Section: Discussionmentioning
confidence: 99%
“…At the imbibition stage, seeds take up increased oxygen amount, resulting in accumulation of ROS shifting the redox state 49 . KNO 3 increases the activity of antioxidant enzymes such as SOD, CAT, ascorbate oxidase (AOX), and peroxidase (POX) in seedlings 49 .…”
Section: Discussionmentioning
confidence: 99%